Iron Deficiency Anemia in Pregnancy: Intravenous Iron Sucrose versus Oral Iron Sulfate - Arzoo, Shabera; Yousof, Shereen; Rahman, Jahanara; Chowdhury, Sameena (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Introduction: Injectable iron sucrose and oral ferrous sulfate both are used for the correctionof anaemia in second and third trimester of pregnancy. But injectable iron is supposed to bemore effective than oral iron, as it needs less time for correction of anaemia and efficacy ismore. Oral iron is cost effective but more time consuming.The objective of the study was to compare the safety of intravenous iron sucrose complex inthe treatment of iron deficiency anemia in third trimester of pregnancy. To compare theefficacy of intravenous iron with oral iron. Method: A randomised controlled trial was conducted in which pregnant women with irondeficiency were sequentially selected from the pregnant women attended antenatal clinic ofOPD of Institute of Child and Maternal Health (ICMH) and assigned either to injectable or tooral ferrous sulfate by random number table. Each study patient was given the total calculatedamount of injectable iron sucrose {Hb deficit (gm/l) × body weight (kg) × 0.24+ storage ironmg } in divided dose 200 mg in 200 ml normal saline intravenously over 1 hour everyalternate day . Each patient of the control group was given ferrous sulfate 200mg orally threetimes a day for 4 weeks. Pregnant women follow up at 4 weeks and 8 weeks after gettreatment by oral and injectable iron. During follow up monitored for adverse effects, clinicaland laboratory response and haemoglobin percentage were observed. Result: There were 75 patients in injectable group and 75 patients in oral group. Injectablegroup achieved a significantly higher Hb level (11.49 ± 0.39) than oral group Hb level (10.39± 0.75) after 8 weeks of treatment. Injectable group showed no major side effects, only twopatient had complains .One patient complain of epigastic pain and one patient complain oftachycardia while in oral group complain of nausea and vomiting, epigastic pain, constipation,allergic reaction was found in 42.0%, 39.3%,35.7% and 3.6% respectively. Conclusion: Iron sucrose complex appears to be a safe and effective in the treatment ofiron deficiency anemia. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 40-44